Impact of the laminar flame speed correlation on the results of a quasi-dimensional combustion model for Spark-Ignition engine. (August 2018) - Teodosio, L.; Bozza, F.; Tufano, D.; Giannattasio, P.; Distaso, E.; Amirante, R.
Abstract: In the present study, the impact of the laminar flame speed correlation on the prediction of the combustion process and performance of a gasoline engine is investigated using a 1D numerical approach. The model predictions are compared with experimental data available for full- and part-load operations of a small-size naturally aspirated Spark-Ignition (SI) engine, equipped with an external EGR circuit. A 1D model of the whole engine is developed in the GT-Power™ environment and is integrated with refined sub-models of the in-cylinder processes. In particular, the combustion is modelled using the fractal approach, where the burning rate is directly related to the laminar flame speed. In this work, three laminar flame speed correlations are assessed, including both experimentally- and numerically-derived formulations, the latter resulting from the fitting of laminar flame speeds computed by a chemical kinetic solver. Each correlation is implemented within the combustion sub-model, which is properly tuned to reproduce the experimental performance of the engine at full load. Then, the reliability of the considered flame speed formulations is proved at part-loads, even under external EGR operations.